Del dicho al hecho: los retos de la democracia ambiental en contextos de extractivismo petrolero en Colombia (2020)
Principle 10 (P10) of the Rio Declaration (1992), proposes a minimalist conception of environmental democracy because the three rights that it raises as foundations (access to information, to participation and to justice) are more procedural than substantial and do not really guarantee environmental democracy. This article presents four cases of environmental licensing of oil blocks in the foothills of the Meta plains, an expanding hydrocarbon extractive frontier in Colombia, where members of local communities activated citizen participation mechanisms (CPM) and legal instruments contemplated in the national legislation to protect their territories, obtaining different results. To identify the factors defined within the exercise of access to rights of environmental democracy that influenced the license granting or denial in these cases (blocks CPO-09, Llanos 69, Llanos 36 and Serranía), a chronology of the CPM activations in every case was made. The comparison of the cases shows that, in those where oil exploration was halted, the results had to do with elements (or democratic practices) outside the structure of environmental democracy, such as articulation with international activist organizations, media outreach and technical information, together with local social mobilization, which are more related to the exercise of environmental justice of social movements.